To Evaluate Serum Eosinophil Cationic Protein and Total IgE Concomitantly May Predict the Persistence of Wheezing in Young Children - Keleş, Esengül (International Scholarly Research Network, 2012)
Background. We investigated the predictive value and the relative risk of the evaluation of serum eosinophilic cationic protein (sECP) and total IgE levels concomitantly in relation to the persistence of wheezing in young children. Methods. The study was conducted prospectively between January 2007 and December 2010. A hundred and eight children, aged between three months and four years, with three or more episodes of wheezing, were studied to evaluate the role of eosinophil inflammation and its relation to persistence of wheezing two years later. Results. A statistically significant difference in terms of total IgE and sECP values was observed between the groups (P < 0.05). When measurement of IgE and sECP was assessed concomitantly, the sensitivity was found to be 92.68%, the negative predictive value was found to be 71.43%, accuracy rate was found to be 84.26%, and the relative risk was found to be 3.06 in group 1. Conclusions. In this study, we aimed to emphasize the importance of the assessment of sECP and total IgE concomitantly, as being two noninvasive and easily applicable tests, useful in predicting persistent wheezing in early childhood.